2022
DOI: 10.1371/journal.pmed.1003928
|View full text |Cite
|
Sign up to set email alerts
|

Monetary incentives and peer referral in promoting secondary distribution of HIV self-testing among men who have sex with men in China: A randomized controlled trial

Abstract: Background Digital network–based methods may enhance peer distribution of HIV self-testing (HIVST) kits, but interventions that can optimize this approach are needed. We aimed to assess whether monetary incentives and peer referral could improve a secondary distribution program for HIVST among men who have sex with men (MSM) in China. Methods and findings Between October 21, 2019 and September 14, 2020, a 3-arm randomized controlled, single-blinded trial was conducted online among 309 individuals (defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…We observed that indexes and alters in both intervention arms were more likely to provide test kits to their peers than those in the standard-of-care arm. This is consistent with the results in studies of secondary distribution of HIVST in China (Sha et al, 2022 ; Zhou et al, 2022 ) and in Uganda (Okoboi et al, 2020 ). We found a higher distribution rate for face-to-face distribution of self-testing kits (S-SST) than the other two arms and a higher rate of returned verified test kits amongst alters in this study arm at primary level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed that indexes and alters in both intervention arms were more likely to provide test kits to their peers than those in the standard-of-care arm. This is consistent with the results in studies of secondary distribution of HIVST in China (Sha et al, 2022 ; Zhou et al, 2022 ) and in Uganda (Okoboi et al, 2020 ). We found a higher distribution rate for face-to-face distribution of self-testing kits (S-SST) than the other two arms and a higher rate of returned verified test kits amongst alters in this study arm at primary level.…”
Section: Discussionsupporting
confidence: 91%
“…This finding differs from the findings in studies on peer distribution of HIVST, which required indexes to order self-testing kits themselves (Lu et al, 2020 ; Wu et al, 2021 ). We did note that the RL-SST arm resulted in a higher numbers of peers being reached compared to the S-SST arm, which aligns with some literature on online peer referral resulting in wider coverage for HIVST (Zhou et al, 2022 ). Subgroup analysis results showed that indexes who were 30 years old or below were more likely to pass along the syphilis testing kits to their peers when compared with standard of care.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, raising awareness of the accuracy and reliability of HIVST in a web-based digital manner might be desirable. In addition, monetary incentives combined with peer referral in the MSM population is also an effective manner to encourage first-time testing [ 73 ]. However, it is essential that other novel and inventive approaches for the promotion of first-time HIV testing are further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches that co-opt members of the community in the delivery of health services through their networks [43][44][45]90,91 Evaluation Community scorecards and quality improvement processes that are led by communities 46,47 Scale-up Approaches that involve training and certification of community members, and allow for shared leadership with community members in the delivery of comprehensive clinical STIs services [48][49][50][51][52][53][54] C where communities are either consulted or lead the development of intervention material or processes, shape clinical service processes or digital health interfaces for STIs, and design research study protocols and workflows. 38 For example, clinical guidelines for STIs services delivery, such as treatment and prevention, have been developed alongside and in consultation with key populations, including MSM and sex workers, in many settings.…”
Section: Deliverymentioning
confidence: 99%